The Planting Media Management on Vegetative Growth of Cassava (Manihotesculentacrantz) - Sinaga, Rosmalina; Siregar, Rolan (International Journal of Environment, Agriculture and Biotechnology, 2021)
The Media Management of Cassava (Manihotesculentacrantz), this research aims to increase the vegetative growth component of cassava clone L-18 SMEs. This research was carried out at an altitude of ± 50 m above sea level, on andosol of pH 5.20. Using Factorial Randomized Block Design (RFBD) as the environmental design with two factors, namely the first factor: tillage treatment with 3 levels: P0 = No tillage, P1 = Minimum tillage, P2 = Perfect tillage and the second factor was the treatment of compost organic matter with 4 levels: B0 = No organic matter (control), B1 = compost organic matter 5 tons/ha, B2 = compost organic matter 10 tons/ha and B3 = compost organic matter 15 tons/ha.The response variables observed and measured were increase in plant height (cm), increase in stem diameter (mm), number of leaf additions (strands), leaf stalk length (cm). The results shows that the management of planting media combined with minimal tillage with the application of 6.02-7.10 tons/ha of organic has a significant effect on the increase of plant height (cm), and the number of leaves (strands). The management of growing media without tillage with the addition of 7.94 tons/ha of organic has a significant effect on the increase of stem diameter (mm), and the addition of 15 tons/ha of organic significantly affected the increase in the number of leaves (strands) and petiole length (cm).